Aerosol characteristics and sources in Yangzhou, China resolved by offline aerosol mass spectrometry and other techniques. (June 2017) - Ge, Xinlei; Li, Ling; Chen, Yanfang; Chen, Hui; Wu, Dan; Wang, Junfeng; Xie, Xinchun; Ge, Shun; Ye, Zhaolian; Xu, Jianzhong; Chen, Mindong
Abstract: Detailed chemical characterization of fine aerosols (PM2.5 ) is important for reducing air pollution in densely populated areas, such as the Yangtze River Delta region in China. This study systematically analyzed PM2.5 samples collected during November 2015 to April 2016 in urban Yangzhou using a suite of techniques, in particular, an Aerodyne soot particle aerosol mass spectrometry (SP-AMS). The techniques used here reconstructed the majority of total PM2.5 measured where extracted species comprised on average 91.2%. Source analyses of inorganic components showed that secondary nitrate, sulfate and chloride were the major species, while primary sources including biomass burning, coal combustion, traffic, industry and re-suspended dust due to nearby demolition activities, could contribute to other species. EC-tracer method estimated that the organic matter (OM) was composed of 65.4% secondary OM (SOM) and 34.6% primary OM (POM), while the SP-AMS analyses showed that the OM was comprised of 60.3% water-soluble OM (WSOM) and 39.7% water-insoluble OM (WIOM). Correlation analyses suggested that WSOM might be rich in secondary organic species, while WIOM was likely mainly comprised of primary organic species. We further conducted positive matrix factorization (PMF) analyses on the WSOM, and identified three primary factors including traffic, cooking and biomass burning, and two secondary factors. We found the secondary factors dominated WSOM mass (68.1%), and their mass contributions increased with the increase of WSOM concentrations. Relatively small contribution of primary sources to WSOM was probably due to their low water solubility, which should be investigated further in future. Overall, our findings improve understanding of the complex aerosol sources and chemistry in this region. Graphical abstract: Highlights: Inorganic species, OM, EC and metals can well reconstruct the PM2.5 mass in Yangzhou. Primary PM2.5 sources included traffic, biomass and coal combustion, industry and dust, etc. Secondary inorganic species dominated PM2.5 mass. WSOM was dominated by secondary organic species. Traffic emissions were likely an important source to organic nitrogen species. Abstract : PM2.5 in Yangzhou was characterized by offline Aerodyne SP-AMS, etc. Secondary inorganic species dominated PM2.5, and SOA dominated water-soluble organics.